Optimal Investment under Uncertainty Regarding Income Subsidies - Tiina Heikkinen (European Regional Science Association (ERSA), 2005)
This paper studies optimal investment in Finnish agriculture under uncertainty regarding future income subsidies. The approach is based on stochastic programming. A multi-stage stochastic programming model is studied, where the farmer has the option to postpone the investment decision. The optimal investment problem is a modified optimal stopping problem. The value of information is evaluated as the difference between the profitability of investment under stable income subsidies and under uncertain subsidies. This difference measures the cost due to imperfect information, reducing the incentive to make investments. The need to maintain productivity enhancing investments in rural regions motivates the development of stable income support programs.
Keywords: 330